Testate amoebae and tintinnids as spatial and seasonal indicators in the intertidal margins of Guadiana Estuary (southeastern Portugal). (November 2015) - Camacho, Sarita; Connor, Simon; Asioli, Alessandra; Boski, Tomasz; Scott, David
Highlights: Testate amoebae and tintinnids from the intertidal margins of Guadiana Estuary. Family Centropyxidae represent 71% of the total individuals. Testate amoebae diversity and faunal density are higher in winter. Living testate amoebae fraction is higher during summer. Living tintinnids only occur in summer, near freshwater and sewage inflows. Abstract: The present study gathers pioneering taxonomical and community data on testate amoebae and agglutinated tintinnids, analyzing their seasonal and spatial distribution patterns in the mesotidal system of the Guadiana Estuary, southeastern Portugal. To evaluate both groups' potential as bioindicators in climate monitoring and paleoenvironmental reconstructions, their abundance, diversity and living proportions were compared to elevation in relation to mean sea-level, marine influence and to periods of elevated water levels. The distributions of testate amoebae and tintinnid total assemblages were also related to major physicochemical variables by means of multivariate analysis. From 49 surface sediment samples collected in winter and summer 2010, 17 species (25 strains) of testate amoebae were identified (in the 63 μm fraction). The Centropyxidae, mainly represented by Centropyxis aculeata, Centropyxis arcula and Centropyxis constricta, had the greatest density (71% of total individuals), while the Difflugidae represented the most species (82% of total species). Higher diversities and densities were observed in winter in the upper estuary, where salinity is negligible, and in the middle estuary where they are concentrated at the lower levels of the intertidal zone. Few or no individuals were observed in the highest marsh zones. In winter, dead testate amoebae were dominant, with empty tests accumulating in the sediments from post-mortem transport by high river discharge. In summer, an increase in the living fraction is observed, with living testate amoebae along the entire estuary, which could indicate that some species are able to live in the lower reaches of the estuary. Along with the testate amoebae, two species of agglutinated tintinnids (>63 μm), Stenosemella ventricosa and Tintinnopsis cf. lata, were abundant in the sediments. Their highest abundances were observed in summer. Living individuals were only recorded in summer, mainly in the vicinities of freshwater and sewage outflows, where elevated nutrient concentrations may be expected. The present study demonstrates that both testate amoebae and tintinnids have well defined patterns in their temporal and spatial distribution, offering high bioindicator potential in environmental/climate monitoring studies as well as in paleoenvironmental reconstructions.